The end of medical confidentiality? Patients, physicians and the state in history. Issue 3 (22nd June 2016) - Rieder, Philip; Louis-Courvoisier, Micheline; Huber, Philippe
Abstract : Medical confidentiality has come under attack in the public sphere. In recent disasters both journalists and politicians have questioned medical confidentiality and claimed that in specific contexts physicians should be compelled to communicate data on their patients' health. The murders of innocent individuals by a suicidal pilot and a Swiss convicted criminal have generated polemical debates on the topic. In this article, historical data on medical confidentiality is used to show that medical practices of secrecy were regularly attacked in the past, and that the nature of medical confidentiality evolved through time depending on physicians' values and judgements. Our demonstration is based on three moments in history. First, at the end of the 16th century, lay authorities put pressure on physicians to disclose the names of patients suffering from syphilis. Second, in the 18th century, physicians faced constant demands for information about patients' health from relatives and friends. Third, employers and insurance companies in the 20th century requested medical data on sick employees. In these three different situations, history reveals that the concept of medical confidentiality was plastic, modelled in the first instance to defend well-to-do patients, in the second instance it was adapted to accommodate the physician's social role and, finally, to defend universal values and public health. Medical secrecy was, and is today, a medical and societal norm that is shaped collectively. Any change in its definition and enforcement was and should be the result of negotiations with all social actors concerned.